Energy-efficient cooling beyond M–cycle: development and evaluation of a two-stage dew-point evaporative cooler - Chen, Zhiyu; Wang, B. C.; Huang, Luofeng; Yang, Z. X.; Cheng, Guanggui; Bui, D. T. (Elsevier, 2025)
The Maisotsenko cycle (M–cycle) enables indirect evaporative cooling of air to near the dew point, offering a low-energy alternative to vapor-compression cooling. However, conventional M–cycle coolers operate as single-stage systems and are limited by high working air ratios (30–50 %), low product air output, and constrained energy efficiency. To address these limitations, a novel two-stage dew-point evaporative cooler (DPEC) was recently proposed, employing sequential wet-bulb and dew-point cooling stages to redistribute the thermal load and enhance performance. This study presents a comprehensive numerical analysis of the two-stage DPEC using a validated three-dimensional COMSOL-based model. The model simulates full-scale air channels under realistic hot and humid conditions and enables direct comparisons with conventional single-stage wet-bulb and M–cycle systems. Results show that the two-stage DPEC achieves a high product air ratio (∼90 %) and dew-point effectiveness up to 95 %, significantly outperforming traditional designs. Key performance metrics—such as cooling capacity, COP, and airflow utilization—are examined across varying climates. The findings confirm the thermodynamic advantages of load partitioning and highlight the system’s potential as a scalable, energy-efficient solution for sustainable cooling in hot regions.
Keywords: Energy; 4012 Fluid mechanics and thermal engineering; 4017 Mechanical engineering